Hypoglycemic Assessment of Aqueous Leaf Extract of Moringa oleifera on Diabetic Wistar Rats - Egbujo Ejike Amina; James O. Adisa; Solomon Matthias Gamde; Etinosa Beauty Omoruyi; Habauka M. Kwaambwa; Lamech M. Mwapagha (Biochemistry Research International)
Conclusion: Leaf extract from Moringa oleifera reduces blood sugar and lessens the damage caused by hyperglycemia in the pancreas and liver.